Penanganan Nilai Kritis pada Pemeriksaan Ureum - Astari Nurisani; Lia Mar’atiningsih; Muuhammad Hadi Sulhan; Gina Nafsa Mutmaina; Sugiah Sugiah; Mamay Mamay; Meti Rizki Utari; Arsylia Intan Zori Ichsani (Jurnal Kesehatan Amanah, 2025)
Critical values ​​in an examination indicate a disorder that requires special and rapid action to improve patient safety. Urea examination is one of the laboratory parameters that functions as an indicator in assessing the level of kidney function. Urea levels are considered critical if the results exceed 100 mg/dl. This study aims to understand how to handle critical values ​​in urea examinations. This study describes a case in the field of clinical chemistry related to critical results obtained from urea examinations. The object of the case study used in this study was a serum sample, with data showing a critical urea level of 185 mg/dl. Based on the confirmation results, this figure is in accordance with the condition of patients who have kidney failure and will undergo hemodialysis therapy. The conclusion of this study shows that handling critical values ​​in urea examinations is carried out by identifying patient identity and ensuring good sample quality. In addition, the sample testing process must be carried out carefully and precisely, control results must be optimal, the reagents used must have the appropriate temperature and not expired, and the equipment must be properly maintained and calibrated. Finally, confirmation and reporting of results must be carried out accurately and on time.